PENCATATAN SEBAGAI SYARAT ATAU RUKUN PERKAWINAN: Kajian Perpaduan Tematik dan Holistik - Nasution, Khoiruddin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
This paper aims to prove that the registration of marriages is one of the requirementsÂ of marriage, which means unregistered marriagesare illegal. The basic reasonsfor this conclusion is two-fold. First, the Prophet Muhammad had commanded public notices of marriage (walimahan, iklan). The purpose of this public notice is to secure the rights of spouses so that couples can achieve the purpose of marriage: a harmonious family. In fact, public notices are means to achieve this. Thus a contextual change is possible to changes the legal form as a mean to achieve the objectives of the marriage. Registration of marriage (marriage certificate) is a kind of contextualization of the command for the public notice of marriage. This contextualization is necessary because it is more effective and efficient to guarantee the achievement of a harmonious family as the ultimate goal of marriage. Second, Indonesian citizens must obey the rules of registration of marriage as set out and defined in the Act no. 1 of 1974 on Marriage [Marriage Act], as it is an implication of the obligation to obey the government (uli al-amr). Therefore, Indonesian citizensÂ who do not comply with the contents of Marriage Act is disobeying the government.Â Furthermore, the Indonesian government has the right to make rules for creating welfare for the community (mashlah), being Indonesian citizens. Consequently, citizens are required to obey rules set by the Indonesian government for the whole welfare of community, and it is clear that the purpose of registration of marriage is for welfare of Indonesian citizens